Pengaruh Literasi Keuangan Syariah, Digital Marketing dan Brand Image terhadap Loyalitas Nasabah Bank Syariah Indonesia - Khofifah Indar Mawar Sari; Weny Rosilawati; Syamsul Hilal (Pajak dan Manajemen Keuangan, 2024)
This research is motivated by the increasing development of sharia banking, the competition in the banking industry will become more competitive and it will become increasingly difficult to maintain customer loyalty. This research aims to analyze the influence of Sharia Financial Literacy, Digital Marketing and Brand Image on customer loyalty. This research is included in Quantitative research. The population of this research was customers of Bank Syariah Indonesia, East OKU Regency, a sample of 96 respondents was taken using calculations using the lemeshow formula. This research data analysis was assisted by using SPSS 26 software to make it easier for researchers to carry out calculations. The results of this research show that sharia financial literacy has a positive and significant effect on customer loyalty with a significance of 0.00 < 0.05, digital marketing has a positive and significant effect on customer loyalty with a significance of 0.00 < 0.05, brand image has a positive and significant effect on customer loyalty with a significance of 0.00 <0.05. The calculated F value is 42,488 and the significant value is 0.00 so that Sharia financial literacy, Digital Marketing and Brand Image simultaneously have a significant positive effect.